Land-price dynamics and macroeconomic fluctuations - Zheng Liu; Pengfei Wang; Tao Zha (Federal Reserve Bank of Atlanta, 2011)
We argue that positive comovements between land prices and business investment are a driving force behind the broad impact of land-price dynamics on the macroeconomy. We develop an economic mechanism that captures the comovements by incorporating two key features into a DSGE model: we introduce land as a collateral asset in firms' credit constraints, and we identify a shock that drives most of the observed fluctuations in land prices. Our estimates imply that these two features combine to generate an empirically important mechanism that amplifies and propagates macroeconomic fluctuations through the joint dynamics of land prices and business investment.
Keywords: E21; E27; E32; E44; 330; land prices; collateral assets; investment; dynamic multiplier; propagation mechanism; co-movements; Grundbesitz; Bodenpreis; Volatilität; Investition; Gesamtwirtschaftliche Produktion; Dynamisches Gleichgewicht